Cnicin: a promising drug for promoting nerve repair - Fischer, Dietmar (Frontiers in Cell and Developmental Biology, 2025)
Traumatic peripheral nerve injuries frequently result in irreversible functional deficits. While neurons possess an intrinsic capacity for axonal regeneration, the temporal constraints and the slow pace of neurite outgrowth often impede the complete restoration of sensory and motor capabilities. This impairment, often culminating in chronic disability, represents a significant clinical challenge, as there are currently no approved pharmacological interventions available to accelerate axon regeneration and improve functional recovery. This perspective focuses on recent scientific advancements that have identified sesquiterpene lactones, a family of naturally derived plant metabolites, as potential therapeutic candidates for treating peripheral nerve trauma. Preclinical investigations employing parthenolide and cnicin have revealed that these compounds can substantially augment axonal extension and functional recovery in diverse in vivo animal paradigms and primary human neuronal cultures. The favorable bioavailability of cnicin following oral administration, coupled with its notable tolerability at dosages considerably largely surpassing the therapeutic range, underscores its substantial potential as an effective pharmacological treatment for addressing the challenges associated with nerve regeneration and restoring sensory and motor functions.